The Student Perception on The Use of Edmodo Based Learning in Writing Instruction - Dinda S, Mawadda; Maming, Khadijah; Rahman, Ali Wira (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
This research was conducted to determine the students' perception of using Edmodo in writing subjects by students of the English Department, Muhammadiyah University of Parepare. This study was also conducted to find out the importance of knowing how the students write properly and correctly according to the writing instructions applied to the Writing Subject of the Department of English, University of Muhammadiyah Parepare based on student perceptions. This study uses a mix methode with a design carried out with students. The population in this study is the students of Department of English, Muhammadiyah University of Parepare. The respondents of this study consisted of eight respondents. In addition, researchers conducted interviews and questionnaires to obtain data. The results of this study indicate that the use of edmodo in distance learning is very effective because edmodo is supported by features that are already in it and is also effective in keeping the class running. However, this application does not support synchronous or face-to-face learning so that there are still shortcomings so students and teachers still have to use other applications to complete the technical learning.